2019
DOI: 10.4274/tjps.galenos.2018.46547
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Estimation of Saxagliptin and Dapagliflozin in Human Plasma by Validated High Performance Liquid Chromatography - Ultraviolet Method

Abstract: Saksagliptin ve dapagliflozinin sabit doz kombinasyonu antidiyabetik ilaç tedavisi için onaylanmıştır ve Qtern markası ile pazarda yer almaktadır. Bu çalışmada amaç, insan plazmasındaki saksagliptin ve dapagliflozinin eş zamanlı tayini için Avrupa Gıda ve İlaç İdaresi kılavuzlarına uygun şekilde linagliptin iç standardı kullanarak ve basit, hızlı, hassas ve validasyonu yapılmış izokroatik ters faz-yüksek performanslı sıvı kromatografi (RP-HPLC) yöntemi geliştirmektir. Gereç ve Yöntemler: Method 4'lü akış pompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Present method was found to be cost-effective owing to utilization of low % (26%) organic mobile phase than latest literature [10]. The analytical run duration for the proposed method is short (6 min); hence, this method was rapid and superior than literature methods [8,[11][12][13].…”
Section: Methods Comparison With Literature Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Present method was found to be cost-effective owing to utilization of low % (26%) organic mobile phase than latest literature [10]. The analytical run duration for the proposed method is short (6 min); hence, this method was rapid and superior than literature methods [8,[11][12][13].…”
Section: Methods Comparison With Literature Methodsmentioning
confidence: 90%
“…Literature survey revealed that there were few reports published on the simultaneous quantification of dapagliflozin and saxagliptin using UV [8], HPTLC [9], HPLC [10][11][12][13][14][15][16][17][18], and LC-MS [19,20] techniques in bulk drug and pharmaceutical dosage forms. Few methods were reported for analysis of dapagliflozin and saxagliptin separately [21][22][23][24] and in combination with other drugs [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…3 respectively: [12][13][14]. After reviewing the literature, it can be said that individual analytical methods [15][16][17][18][19][20][21][22][23][24] are available for Metformin HCl, Dapagliflozin and Saxagliptin however, no RP-HPLC method is available for simultaneous estimation of Metformin HCL, Dapagliflozin and Saxagliptin in pharmaceutical dosage from as FDC. Developing Stability indicating RP-HPLC method for simultaneous estimation of Metformin HCl, Dapagliflozin and Saxagliptin in pharmaceutical dosage from as FDC is both requirement and challenge.…”
Section: Introduction [1-11]mentioning
confidence: 99%
“…) that acts as a sodium inhibitor of glucose co‐transporters Based on a survey of the published literature (Supporting Information Tables S1 and S2), some methods described DGF quantification either in its pure form or in its tablet dosage form for use in assays and/or stability studies. These methods included spectrophotometric and chromatographic methods , but suffered from either low sensitivity or difficulty, or high cost of analysis. A new simple, cheap and sensitive method is therefore urgently needed for analysis of DGF in both bulk and its commercially dosage forms to establish as a quality control.…”
Section: Introductionmentioning
confidence: 99%
“…These methods included spectrophotometric and chromatographic methods [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] , but suffered from either low sensitivity or difficulty, or high cost of analysis. A new simple, cheap and sensitive method is therefore urgently needed for analysis of DGF in both bulk and its commercially dosage forms to establish as a quality control.…”
Section: Introductionmentioning
confidence: 99%